2023
DOI: 10.1007/s00382-023-06717-7
|View full text |Cite
|
Sign up to set email alerts
|

Downstream development during ridging South Atlantic Ocean anticyclones

Abstract: Ridging South Atlantic high pressure systems (ridging highs) are often accompanied by cut-off low (COL) pressure systems aloft, but may also occur without them, in which case a linear baroclinic wave would be observed propagating across the South African domain in the upper troposphere. Using 41 years of ERA-5 reanalysis data, this study documents differences between the characteristics of the prevailing dynamical processes and associated local eddy kinetic energy generation, its downstream transfer and dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Why some waves in the South African domain enter non-linear regimes and others remain in more linear regimes is still an open question. However, Ndarana et al (2023) showed that baorclinic conversion observed during the letter is less intense that in the case of former, meaning that when COLs (in general wave breaking) do not occur it is suppressed.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Why some waves in the South African domain enter non-linear regimes and others remain in more linear regimes is still an open question. However, Ndarana et al (2023) showed that baorclinic conversion observed during the letter is less intense that in the case of former, meaning that when COLs (in general wave breaking) do not occur it is suppressed.…”
Section: Introductionmentioning
confidence: 93%
“…Linear Waves the weaker increase in eddy kinetic energy generation during linear-regime waves in the South African domain (Ndarana et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4c). These anomalies indicate the presence of extratropical waves that can favour precipitation (Ivanciu et al, 2022;Ndarana et al, 2022Ndarana et al, , 2023, through their effects on the AL (Pascale et al, 2019).…”
Section: The Effect Of Internal Climate Variabilitymentioning
confidence: 99%